2021
DOI: 10.3390/nano11102477
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite PLA/C20A Nanoclay by Ultrasound-Assisted Melt Extrusion for Adsorption of Uremic Toxins and Methylene Blue Dye

Abstract: Design of functional materials it is of great importance to address important problems in the areas of health and environment. In the present work, the synthesis and application of poly-meric nanocomposite materials with poly (lactic acid) (PLA) and modified nanoclay (cloisite 20A) with 1,4-diaminobutane dihydrochloride at different reaction times were studied. The concentra-tions of the nanoclays in the PLA matrix were 0.5, 1 and, 5% by weight (wt%). TGA showed that sample C20AM 120 (120 min of treatment) obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The values of R 2 in the case of the MB dye were closer to 1 than the Langmuir isotherm, which suggests that it better describes the adsorption process, there are homogeneous adsorption sites forming a single layer. 44 On the other hand, in the rhodamine B dye, a different model is suggested by the Freundlich isotherm, which is based on the fact that the concentration on the surface of the adsorbent increases as the concentration of the adsorbate increases, describing a multilayer adsorption process for heterogeneous surfaces. 45,46 3.6.3 Desorption studies.…”
Section: Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…The values of R 2 in the case of the MB dye were closer to 1 than the Langmuir isotherm, which suggests that it better describes the adsorption process, there are homogeneous adsorption sites forming a single layer. 44 On the other hand, in the rhodamine B dye, a different model is suggested by the Freundlich isotherm, which is based on the fact that the concentration on the surface of the adsorbent increases as the concentration of the adsorbate increases, describing a multilayer adsorption process for heterogeneous surfaces. 45,46 3.6.3 Desorption studies.…”
Section: Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…This indicates that at this weight percentage there is a greater compatibility between the ZnO and TiO 2 particles modified with lactic acid with the PLA polymeric matrix. Studies of PLA and nanoparticles such as modified nanoclays, through ultrasound-assisted extrusion, have shown that adding modified nanoparticles to some functional groups increases the thermal stability of polymeric nanocomposites [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a shows six peaks for the C20A sample, 2θ $ 3.3 -3.7 , 72 6.6 -7.1 , 73 19.9 -20.7 , 24.6 , and 35.8 . 74 From Figure 5a, the most intense peak for C20A is 2θ $ 3.6 , 72 the most common peak of nanoclay in the literature. Resner and co-workers described that the characteristic peak of 2θ $ 3.6 refers to the gallery spacing (001) of the C20A, depending on the modification.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 97%